Competing eBook acquisition models: which model best serves a community college library?. (12th December 2019) - LaMagna, Michael; Swenson Danowitz, Erica; Rodgers, Andrea
Abstract : Purpose: Academic libraries continue to invest in eBooks to ensure access to content in various formats. This paper aims to examine eBook acquisition models, including patron-driven acquisitions, one-time purchases, focused collection subscriptions or large-scale subscriptions, to better understand how users engage with this content based on usage data. Design/methodology/approach: Usage data provide insights into eBook acquisition and how access models influence use. This study defines the acquisition model for each eBook purchase. Data were examined to determine usage by acquisition model and cost-per-use. Findings: This paper finds that for a large suburban community college, a large-scale subscription model has the lowest cost-per-use and serves the largest portion of students. Focused collection subscriptions supported small, specialized programs in the Allied Health, Emergency Services, and Nursing fields. Originality/value: This paper examines how eBooks are acquired to determine which model best serves an academic library community, specifically a community college library, which is currently underrepresented in the literature.